1988
DOI: 10.1029/jd093id02p01564
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric methane from an Amazonian floodplain lake

Abstract: During July and August 1985, the sources of methane and its flux to the troposphere were measured from a houseboat laboratory anchored in Lago Calado, a stratified, dendritic lake of about 6 km 2 area, located in the central Amazon basin. Methane concentrations in the mixed layer of the lake were varied (0.0001-0.0055 mM) and usually less than 0.004 mM CH,•, with no consistant temporal trend. Methane concentrations increased with depth across the thermocline as oxygen dropped to less than 0.1 mg O 2 L -x. Over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
96
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 149 publications
(107 citation statements)
references
References 21 publications
(6 reference statements)
8
96
1
1
Order By: Relevance
“…The diurnal cycle of FCH 4 is presented in detail by Podgrajsek et al (2014) where it was suggested that the onset of a diurnal cycle of FCH 4 was controlled by water-side convection and formation of methane in the sediment. Such a pattern with convective driven high night-time fluxes was previously observed using flux chambers (Crill et al, 1988;Godwin et al, 2013), while studies from other lakes have found higher daytime CH 4 emissions (e.g. Bastviken et al, 2004Bastviken et al, , 2010Keller and Stallard, 1994).…”
Section: Eddy Covariance Methodsmentioning
confidence: 80%
“…The diurnal cycle of FCH 4 is presented in detail by Podgrajsek et al (2014) where it was suggested that the onset of a diurnal cycle of FCH 4 was controlled by water-side convection and formation of methane in the sediment. Such a pattern with convective driven high night-time fluxes was previously observed using flux chambers (Crill et al, 1988;Godwin et al, 2013), while studies from other lakes have found higher daytime CH 4 emissions (e.g. Bastviken et al, 2004Bastviken et al, , 2010Keller and Stallard, 1994).…”
Section: Eddy Covariance Methodsmentioning
confidence: 80%
“…Another possibility is increased root leakage of substrates for methanogenesis during daytime. The opposite diel patterns has been observed in a deeper wind-sheltered tropical lake which became stratified and accumulated CH4 in anoxic bottom water during daytime, while nighttime convection transported the accumulated CH4 to the surface waters resulting in elevated night-time emissions (Crill et al 1988). It has been suggested that methanotrophs could be inhibited by light (Dumestre et al 1999;Murase and Sugimoto 2005) but presumably this would have a limited effect on methane oxidation in surface sediments.…”
Section: Discussionmentioning
confidence: 98%
“…5a3-b3 As WWM is sensitive to different wetland types through the plant-mediated transport mechanism that depends on the vegetation type (Walter et al, 2001a), locations with three Bartlett et al (1988) who estimated the ebullitive flux to account for 48 % in open water and 54 % in flooded forest areas, the ebullitive contribution of WWM to the CH 4 transport to the atmosphere is in the same order of magnitude. However, Crill et al (1988) estimated 70 % contribution of ebullition. Up to this study WWM has only been validated against observations from a swamp region in Panama in the tropics (Walter and Heimann, 2000).…”
Section: Wetland Fluxesmentioning
confidence: 99%